148k views
5 votes
What is the answer?
2(x + 3) = x - 4

User AAlferez
by
4.9k points

2 Answers

4 votes

Answer:

-10

Explanation:

take out the parantheses

2x + 6 = x - 4

Put the variable on the left side of the ecuation with the opposite sign

2x + 6 -x = -4

Put the six on the right side of the equation and change the sign

2x - x = - 4 - 6

simplify

x = - 4 - 6

x = -10

User Rhellem
by
4.3k points
3 votes

Answer:

-10

Explanation:

User Atazmin
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.